Bio-Conversion of Waste Paper Into Fermentable Sugars—A Review - Ojewumi, Modupe E.; Emetere, Moses E.; Obanla, Oyinlola R.; Babatunde, Damilola E.; Adimekwe, Ebuka G. (Frontiers in Chemical Engineering, 2022)
Pollution generated by solid waste has become a massive source of concern worldwide as the amount of waste being generated has become overwhelming. Waste paper contributes significantly to the overall solid municipal waste being generated daily and with control methods that are equally bad for the environment or just plain ineffective; better, effective, and environmentally friendly control solutions are required. This study reviews the use of various microorganisms as they aid in the control of waste papers in an environmentally conscious way. In addition to being an environmentally friendly solution to the issue of solid waste paper pollution, it is also a prominent source of renewable energy in the conversion of paper into fermentable sugars for the production of bio-ethanol. This review examines the vital revolution in the enzymatic hydrolysis of paper to sugar. Salient challenges that involve bioconversion were highlighted and a few solutions were suggested.